Begomovirus susceptibility in wild Nicaraguan tomato populations - Rasmusson, Karin (SLU/Dept. of Plant Biology and Forest Genetics (until 131231), 2010)

(untitled)
Tomato production is a common and important agricultural activity in Nicaragua. During the last decades tomato producers have suffered great yield losses due to begomoviruses (family Geminiviridae). The genome of begomoviruses generally consists of two circular ssDNA components, DNA-A and DNA-B. Tomato yellow leaf curl virus (TYLCV) is an example of a begomovirus with only one component. An approach to manage the virus epidemics has been to breed a cultivar with begomovirus resistance genes, which have been transferred from wild tomato. The objective of this project was to investigate the begomovirus susceptibility of 20 wild tomato populations, with the aim to find a population with resistance. As an additional aim the presence of mixed begomovirus infections in the plants was investigated. Mixed infections are a driving force in begomovirus evolution. In order to detect begomoviruses in the tomato samples polymerase chain reaction (PCR) was run, using the degenerate primer pair AV494 and AC1048. In order to determine the presence of mixed infections in the samples rolling circle amplification (RCA) was carried out. Subsequently, the amplified DNA was digested by the restriction enzymes SalI, HpaII and EcoRI in order to determine the number of begomovirus components in each sample. No mixed infections were detected in the plants. In some of the investigated samples only one begomovirus component was detected. All wild tomato plants were found to be susceptible to begomovirus infections. However, one of the populations was not as easily infected as the other, and showed relatively mild symptoms after infection. In order to determine if this genotype could be used for breeding purposes, it is necessary to investigate if it has any of the genes previously found to be associated with begomovirus resistance, or a previously unknown resistance gene. Moreover, if resistance is detected it is essential to determine to which begomovirus species the genotype is resistant.